Lipoprotein(a) Levels and Isoforms and Fibrinolytic Activity in Postmenopause – Influence of Hormone Replacement Therapy - Estellés, Amparo; Cano, Antonio; Falcó, Cristina; España, Francisco; Gilabert, Juan; Grancha, Salvador; Aznar, Justo (Thrombosis and Haemostasis, 1999)
Epidemiological studies suggest that hormone replacement therapy (HRT) decreases the risk of cardiovascular disease in postmenopausal women via several mechanisms, including modifications in the fibrinolytic system and lipoprotein(a) [Lp(a)] levels. The aim of this study was to examine the influence of the levels and isoforms of Lp(a) on fibrinolytic activity in 91 postmenopausal women in comparison with premenopause and analyze the effect of HRT on those parameters. In postmenopause, an increase in plasma Lp(a) and plasminogen activator inhibitor-1 (PAI-1) levels was found. A significant inverse correlation was observed between Lp(a) or PAI-1 levels and plasmin generation. Plasma samples with low molecular weight (MW) apo(a) isoforms showed higher plasmin inhibition than plasmas with high MW apo(a) isoforms and similar levels of total Lp(a) and PAI-1. HRT induced a significant decrease in Lp(a) and PAI-1 levels and an increase in estradiol levels, as well as an increase in fibrinolytic activity. A significant correlation was found between the percentages of variation in Lp(a) levels and in plasmin generation and between the percentages of variation in PAI-1 levels and in the euglobulin lysis time under HRT. In conclusion, the increase in fibrinolytic activity observed in women under HRT could be explained by two independent mechanisms: (a) the decrease in PAI-1 and (b) the decrease in the inhibition of plasmin generation due to the decrease in Lp(a) levels.